High-voltage ceramic insulator and preparation method thereof

By using specific components and processes to prepare high-voltage ceramic insulators, the problem of insulator damage in saline-alkali environments has been solved, and the corrosion resistance and mechanical properties have been improved, thus extending the service life.

CN121122853AInactive Publication Date: 2025-12-12HENAN PROVINCE ZHONGLIANHONGXING ELECTRICAL PORCELAIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511385492.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-12-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

High-voltage ceramic insulators are easily damaged in saline-alkali environments, resulting in a shortened service life. Existing technologies are unable to effectively improve their wear resistance and mechanical properties.

Method used

High-voltage ceramic insulators are prepared using alumina, zirconium oxide, bauxite, quartz sand, potassium feldspar, kaolin, dicalcium phosphate, magnesium chloride, zinc oxide, and barium carbonate as matrix materials, combined with hexagonal boron nitride-titanium dioxide modifiers and lanthanum-basalt fiber composites through a specific process, thereby enhancing their corrosion resistance and mechanical properties.

Benefits of technology

It improves the corrosion resistance and mechanical properties of insulators, and extends their service life in saline-alkali environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-voltage ceramic insulator and a preparation method thereof, and belongs to the technical field of high-voltage insulator preparation, and the high-voltage ceramic insulator comprises the following components: aluminum oxide, zirconium oxide, bauxite, quartz sand, potassium feldspar, kaolin, calcium hydrophosphate, magnesium chloride, zinc oxide and barium carbonate which are used as insulator base materials, the hexagonal boron nitride-titanium dioxide modifier and the lanthanum-basalt composite fiber are used as functional materials. The high-voltage ceramic insulator prepared by the technical scheme of the invention has excellent mechanical properties and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-voltage insulator preparation technology, specifically relating to a high-voltage ceramic insulator and its preparation method. Background Technology

[0002] With the rapid development of the power system, the safety and reliability of high-voltage transmission lines, as the core equipment for power transmission, are of paramount importance.

[0003] Ceramic insulators, with their excellent electromechanical properties, have long been widely used in high-voltage capacitors, serving functions such as insulation, sealing, and support. During actual operation, high-voltage capacitors are subjected to harsh environmental conditions such as heavy rain, high humidity, and strong winds, which can damage the insulator's base structure and severely shorten its service life, especially in saline-alkali environments.

[0004] Enhancing the wear resistance and mechanical properties of insulators in saline-alkali environments is one way to extend their service life. Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a high-voltage ceramic insulator and its preparation method.

[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A high-voltage ceramic insulator, by weight, comprises the following components: 25-30 parts alumina, 5-10 parts zirconium oxide, 20-30 parts bauxite, 20-30 parts quartz sand, 10-20 parts potassium feldspar, 15-20 parts kaolin, 10-20 parts dicalcium phosphate, 4-6 parts magnesium chloride, 2-4 parts zinc oxide, and 1-3 parts barium carbonate as the insulator matrix material; and 0.5-1 parts hexagonal boron nitride-titanium dioxide modifier and 1-2 parts graphene oxide-basalt fiber composite as functional materials.

[0007] Furthermore, the preparation method of the hexagonal boron nitride-titanium dioxide modified material includes the following steps: dispersing hexagonal boron nitride in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.2-0.3 g / mL; adding titanium tetrachloride to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.06-0.065 g / mL; magnetically stirring for 30 min; adding the hexagonal boron nitride dispersion; then adding sodium hydroxide solution dropwise to adjust the pH value to 6; stirring and reacting for 30 min; then pouring into a hydrothermal reactor and heating to 180℃ and holding for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified material.

[0008] Furthermore, the mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.7-1.75.

[0009] Furthermore, the preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers are soaked in acetone for 1.5-2 hours at room temperature, dried at 100-110℃ for 1-1.5 hours, soaked in nitric acid solution in a constant temperature water bath for 2-2.5 hours, washed 4 times with distilled water, and then dried to obtain acidified basalt fibers. S2: Take a lanthanum chloride solution, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

[0010] Furthermore, the concentration of the lanthanum chloride solution is 0.5-0.6 mol / L.

[0011] A method for preparing a high-voltage ceramic insulator as described above includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8-8.5, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 20-30 minutes, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material; A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.1-1% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 20-30 minutes, vacuum filter, wash, dry, grind and then add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 5-8 hours to obtain the blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 300-450℃ at a rate of 5-20℃ / h, then heated to 980-1050℃ at a rate of 50-100℃ / h and held for 5-10h, then heated to 1280-1350℃ at a rate of 20-50℃ / h and held for 1-4h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part; A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

[0012] Furthermore, the mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified material and tris(hydroxymethyl)aminomethane solution in A1 is (2-3):1:(18-19).

[0013] Furthermore, the mass concentration of the tris(hydroxymethyl)aminomethane solution is 9-10%.

[0014] Furthermore, the silane coupling agent is aminopropyltriethoxysilane.

[0015] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art: 1. Basalt fibers possess high strength and corrosion resistance, and lanthanum inlay further enhances their corrosion resistance. Dopamine hydrochloride, under alkaline conditions, forms polydopamine with extremely strong adhesion. This polydopamine is then used to coat the hexagonal boron nitride-titanium dioxide composite. Through π-π interactions, the dopamine adheres tightly to the surface of the hexagonal boron nitride. Then, a silane coupling agent tightly binds the lanthanum-basalt composite fibers. Lanthanum forms a dense oxide layer on the basalt surface, preventing the intrusion of water, oxygen, and corrosive ions from damaging the hexagonal boron nitride-titanium dioxide composite. This further increases the corrosion resistance and mechanical properties of the prepared insulator, improving its corrosion resistance in saline-alkali environments.

[0016] 2. In the preparation of hexagonal boron nitride-titanium dioxide modified materials, titanium tetrachloride is hydrolyzed in situ on the surface of hexagonal boron nitride, which can enhance the dispersibility of hexagonal boron nitride in the insulator matrix material and the interfacial bonding force with the insulator matrix material, improve the corrosion resistance and mechanical properties of the insulator matrix material, and enhance its corrosion resistance in saline-alkali environments. Detailed Implementation

[0017] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0018] Example 1 A high-voltage ceramic insulator, by weight, comprises the following components: 25 parts alumina, 7 parts zirconium oxide, 25 parts bauxite, 25 parts quartz sand, 15 parts potassium feldspar, 15 parts kaolin, 15 parts dicalcium phosphate, 5 parts magnesium chloride, 3 parts zinc oxide, and 2 parts barium carbonate as the insulator matrix material; 0.75 parts hexagonal boron nitride-titanium dioxide modifier and 1.5 parts lanthanum-basalt composite fiber as functional materials.

[0019] The preparation method of the hexagonal boron nitride-titanium dioxide modified material includes the following steps: Hexagonal boron nitride was dispersed in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.25 g / mL. Titanium tetrachloride was added to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.06 g / mL. After magnetic stirring for 30 min, the hexagonal boron nitride dispersion was added. Then, sodium hydroxide solution was added dropwise to adjust the pH value to 6, and the reaction was stirred for 30 min. Finally, the mixture was poured into a hydrothermal reactor and heated to 180℃ and kept at that temperature for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified product.

[0020] The mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.75.

[0021] The preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers were soaked in acetone for 2 hours at room temperature, dried at 105°C for 1.5 hours, soaked in nitric acid solution in a constant temperature water bath for 2 hours, washed 4 times with distilled water, and dried to obtain acidified basalt fibers. S2: Take a 0.6 mol / L lanthanum chloride solution, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

[0022] The method for preparing the high-voltage insulator includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8.5, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 25 min, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material. A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.5% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 25 minutes, vacuum filter, wash, dry, grind and then add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 6.5 hours to obtain the blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 400℃ at a rate of 15℃ / h, then heated to 1020℃ at a rate of 70℃ / h and held for 7.5h, then heated to 1310℃ at a rate of 35℃ / h and held for 2h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part. A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

[0023] In S1, the mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified material, and tris(hydroxymethyl)aminomethane solution is 2.5:1:18, and the mass concentration of tris(hydroxymethyl)aminomethane solution is 9.5%.

[0024] Example 2 A high-voltage ceramic insulator, by weight, comprises the following components: 25 parts alumina, 5 parts zirconium oxide, 20 parts bauxite, 20 parts quartz sand, 10 parts potassium feldspar, 15 parts kaolin, 10 parts dicalcium phosphate, 4 parts magnesium chloride, 2 parts zinc oxide, and 1 part barium carbonate as the insulator matrix material; 0.5 parts hexagonal boron nitride-titanium dioxide modifier and 1 part lanthanum-basalt composite fiber as functional materials.

[0025] The preparation method of the hexagonal boron nitride-titanium dioxide modified material includes the following steps: Hexagonal boron nitride was dispersed in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.2 g / mL. Titanium tetrachloride was added to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.06 g / mL. After magnetic stirring for 30 min, the hexagonal boron nitride dispersion was added. Then, sodium hydroxide solution was added dropwise to adjust the pH value to 6, and the reaction was stirred for 30 min. The mixture was then poured into a hydrothermal reactor and heated to 180℃ and kept at that temperature for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified product.

[0026] The mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.7.

[0027] The preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers were soaked in acetone for 1.5 hours at room temperature, dried at 100°C for 1 hour, soaked in nitric acid solution in a constant temperature water bath for 2 hours, washed 4 times with distilled water, and dried to obtain acidified basalt fibers. S2: Take a 0.5 mol / L lanthanum chloride solution, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

[0028] The method for preparing the high-voltage insulator includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 20 min, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material. A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.1% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 20 minutes, vacuum filter, wash, dry, grind, add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 5 hours to obtain blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 300℃ at a rate of 5℃ / h, then heated to 980℃ at a rate of 50℃ / h and held for 5h, then heated to 1280℃ at a rate of 20℃ / h and held for 1h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part. A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

[0029] The mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified compound, and tris(hydroxymethyl)aminomethane solution in S1 is 2:1:18, and the mass concentration of tris(hydroxymethyl)aminomethane solution is 9%.

[0030] Example 3 A high-voltage ceramic insulator, by weight, comprises the following components: 30 parts alumina, 10 parts zirconium oxide, 30 parts bauxite, 30 parts quartz sand, 20 parts potassium feldspar, 20 parts kaolin, 20 parts dicalcium phosphate, 6 parts magnesium chloride, 4 parts zinc oxide, and 3 parts barium carbonate as the insulator matrix material; 1 part hexagonal boron nitride-titanium dioxide modifier and 2 parts lanthanum-basalt composite fiber as functional materials.

[0031] The preparation method of the hexagonal boron nitride-titanium dioxide modified material includes the following steps: Hexagonal boron nitride was dispersed in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.3 g / mL. Titanium tetrachloride was added to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.065 g / mL. After magnetic stirring for 30 min, the hexagonal boron nitride dispersion was added. Then, sodium hydroxide solution was added dropwise to adjust the pH value to 6, and the reaction was stirred for 30 min. The mixture was then poured into a hydrothermal reactor and heated to 180℃ and kept at that temperature for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified product.

[0032] The mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.75.

[0033] The preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers were soaked in acetone for 2 hours at room temperature, dried at 110°C for 1.5 hours, soaked in nitric acid solution in a constant temperature water bath for 2.5 hours, washed 4 times with distilled water, and dried to obtain acidified basalt fibers. S2: Take a 0.6 mol / L lanthanum chloride solution, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

[0034] The method for preparing the high-voltage insulator includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8.5, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 30 min, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material; A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.1-1% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 20-30 minutes, vacuum filter, wash, dry, grind and then add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 5-8 hours to obtain the blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 450℃ at a rate of 20℃ / h, then heated to 1050℃ at a rate of 100℃ / h and held for 10h, then heated to 1350℃ at a rate of 50℃ / h and held for 4h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part. A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

[0035] The mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified compound, and tris(hydroxymethyl)aminomethane solution in S1 is 3:1:19, and the mass concentration of tris(hydroxymethyl)aminomethane solution is 10%.

[0036] Example 4 A high-voltage ceramic insulator, by weight, comprises the following components: 26 parts alumina, 6 parts zirconium oxide, 23 parts bauxite, 22 parts quartz sand, 13 parts potassium feldspar, 16 parts kaolin, 13 parts dicalcium phosphate, 4.5 parts magnesium chloride, 2.5 parts zinc oxide, and 1.3 parts barium carbonate as the insulator matrix material; 0.6 parts hexagonal boron nitride-titanium dioxide modifier and 1.2 parts lanthanum-basalt composite fiber as functional materials.

[0037] The preparation method of the hexagonal boron nitride-titanium dioxide modified material includes the following steps: Hexagonal boron nitride was dispersed in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.23 g / mL. Titanium tetrachloride was added to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.063 g / mL. After magnetic stirring for 30 min, the hexagonal boron nitride dispersion was added. Then, sodium hydroxide solution was added dropwise to adjust the pH value to 6, and the reaction was stirred for 30 min. Finally, the mixture was poured into a hydrothermal reactor and heated to 180℃ and kept at that temperature for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified product.

[0038] The mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.72.

[0039] The preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers were soaked in acetone for 1.6 h at room temperature, dried at 103 °C for 1.1 h, soaked in nitric acid solution in a constant temperature water bath for 2.2 h, washed 4 times with distilled water, and dried to obtain acidified basalt fibers. S2: Take a lanthanum chloride solution with a concentration of 0.53 mol / L, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

[0040] The method for preparing the high-voltage insulator includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8.2, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 23 min, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material; A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.3% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 23 minutes, vacuum filter, wash, dry, grind and then add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 5.5 hours to obtain the blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 320℃ at a rate of 8℃ / h, then heated to 1000℃ at a rate of 60℃ / h and held for 6h, then heated to 1290℃ at a rate of 25℃ / h and held for 1.5h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part. A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

[0041] The mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified material, and tris(hydroxymethyl)aminomethane solution in S1 is 2.3:1:18.4, and the mass concentration of tris(hydroxymethyl)aminomethane solution is 9.4%.

[0042] Example 5 A high-voltage ceramic insulator, by weight, comprises the following components: 29 parts alumina, 9 parts zirconium oxide, 28 parts bauxite, 28 parts quartz sand, 18 parts potassium feldspar, 18 parts kaolin, 19 parts dicalcium phosphate, 5.5 parts magnesium chloride, 3.5 parts zinc oxide, and 2.5 parts barium carbonate as the insulator matrix material; 0.8 parts hexagonal boron nitride-titanium dioxide modifier and 1.8 parts lanthanum-basalt composite fiber as functional materials.

[0043] The preparation method of the hexagonal boron nitride-titanium dioxide modified material includes the following steps: Hexagonal boron nitride was dispersed in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.28 g / mL. Titanium tetrachloride was added to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.064 g / mL. After magnetic stirring for 30 min, the hexagonal boron nitride dispersion was added. Then, sodium hydroxide solution was added dropwise to adjust the pH value to 6, and the reaction was stirred for 30 min. The mixture was then poured into a hydrothermal reactor and heated to 180℃ and kept at that temperature for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified product.

[0044] The mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.74.

[0045] The preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers were soaked in acetone for 1.8 h at room temperature, dried at 108 °C for 1.4 h, soaked in nitric acid solution in a constant temperature water bath for 2.4 h, washed 4 times with distilled water, and dried to obtain acidified basalt fibers. S2: Take a lanthanum chloride solution with a concentration of 0.58 mol / L, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

[0046] The method for preparing the high-voltage insulator includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8.4, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 28 min, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material; A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.8% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 28 minutes, vacuum filter, wash, dry, grind, add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 7.5 hours to obtain blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 430℃ at a rate of 18℃ / h, then heated to 1020℃ at a rate of 90℃ / h and held for 9h, then heated to 1340℃ at a rate of 45℃ / h and held for 3.5h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part. A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

[0047] The mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified material, and tris(hydroxymethyl)aminomethane solution in S1 is 2.8:1:18.8, and the mass concentration of tris(hydroxymethyl)aminomethane solution is 9-10%.

[0048] Comparative Example 1 differs from Example 1 in that it does not coat the hexagonal boron nitride-titanium dioxide composite, i.e., it does not add dopamine hydrochloride.

[0049] The difference between Comparative Example 2 and Example 1 is that lanthanum chloride was not added in the preparation of the lanthanum-basalt fiber composite.

[0050] The difference between Comparative Example 3 and Example 1 is that lanthanum chloride was not added during the preparation of the lanthanum-basalt fiber composite without the addition of dopamine hydrochloride.

[0051] 1. The mechanical properties of the insulators prepared in the examples and comparative examples were tested, and the results are shown in Table 1. 2. Corrosion resistance tests were conducted on the insulators prepared in the examples and comparative examples. The corrosion resistance was characterized by a chloride ion immersion test. The test method was as follows: a sodium chloride aqueous solution with a solute mass percentage of 3.5% was prepared as the corrosion solution. The mass m0 of the test sample before immersion was weighed. Then, the entire test sample was immersed in the sodium chloride aqueous solution (solid-liquid mass ratio of solid / liquid = 1:50). After immersion at room temperature for 30 days, the sample was washed three times in deionized water using an ultrasonic cleaner to remove residual solution from the sample surface. Then, it was dried in an oven at 80℃ for 2 hours and air-cooled to room temperature. The mass m1 of the sample was then tested. The mass loss before and after corrosion was calculated as Δm = m0 - m1. The results are shown in Table 1 below.

[0052] Table 1

[0053] In conjunction with Examples 1-5 and Table 1, the high-voltage ceramic insulator prepared by the technical solution of the present invention has good corrosion resistance and mechanical properties.

[0054] Based on Example 1, Comparative Example 1, and the data in Table 1, it can be seen that the coating of hexagonal boron nitride-titanium dioxide composite with dopamine can increase the corrosion resistance and mechanical properties of its insulators.

[0055] Based on the data from Example 1, Comparative Example 2, and Table 1, it can be seen that the insertion of lanthanum into the lanthanum-basalt fiber composite can improve its corrosion resistance.

[0056] Based on the data from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 and Table 1, it can be seen that the loss of the product in Comparative Example 3 is significantly higher than that in Comparative Example 1 and Comparative Example 2, and the surface of the product is significantly more severely corroded than that in Comparative Example 2 and Comparative Example 3. The insertion of lanthanum into the lanthanum-basalt fiber composite and the coating of hexagonal boron nitride by dopamine have a synergistic effect in improving the corrosion resistance of the product.

[0057] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high-voltage ceramic insulator, characterized in that: By weight, it includes the following components: 25-30 parts alumina, 5-10 parts zirconium oxide, 20-30 parts bauxite, 20-30 parts quartz sand, 10-20 parts potassium feldspar, 15-20 parts kaolin, 10-20 parts dicalcium phosphate, 4-6 parts magnesium chloride, 2-4 parts zinc oxide, and 1-3 parts barium carbonate as insulator matrix materials; 0.5-1 parts hexagonal boron nitride-titanium dioxide modifier and 1-2 parts graphene oxide-basalt fiber composite as functional materials.

2. The high-voltage ceramic insulator according to claim 1, characterized in that: The preparation method of the hexagonal boron nitride-titanium dioxide modified compound includes the following steps: dispersing hexagonal boron nitride in deionized water to prepare a hexagonal boron nitride dispersion with a concentration of 0.2-0.3 g / mL; adding titanium tetrachloride to deionized water to prepare a titanium tetrachloride dispersion with a concentration of 0.06-0.065 g / mL; magnetically stirring for 30 min; adding the hexagonal boron nitride dispersion; then adding sodium hydroxide solution dropwise to adjust the pH value to 6; stirring and reacting for 30 min; then pouring into a hydrothermal reactor and heating to 180℃ and holding for 10 h to obtain the hexagonal boron nitride-titanium dioxide modified compound.

3. A high-voltage ceramic insulator according to claim 2, characterized in that: The mass ratio of hexagonal boron nitride to titanium tetrachloride is 1:1.7-1.

75.

4. A high-voltage ceramic insulator according to claim 1, characterized in that: The preparation method of the lanthanum-basalt composite fiber includes the following steps: S1: Basalt fibers are soaked in acetone for 1.5-2 hours at room temperature, dried at 100-110℃ for 1-1.5 hours, soaked in nitric acid solution in a constant temperature water bath for 2-2.5 hours, washed 4 times with distilled water, and then dried to obtain acidified basalt fibers. S2: Take a lanthanum chloride solution, then soak the acidified basalt fiber in the lanthanum chloride solution for 2 hours, and then dry it to obtain lanthanum-basalt composite fiber.

5. A high-voltage ceramic insulator according to claim 4, characterized in that: The concentration of the lanthanum chloride solution is 0.5-0.6 mol / L.

6. A method for preparing a high-voltage ceramic insulator according to any one of claims 1-5, characterized in that: Includes the following steps: A1: Take a tris(hydroxymethyl)aminomethane solution, add an appropriate amount of hydrochloric acid until the pH value is 8-8.5, then add hexagonal boron nitride-titanium dioxide modified material and ultrasonically disperse for 20-30 minutes, then add hydrochloric acid dopamine solution, heat and stir, then vacuum filter, wash, dry, and grind to obtain the coated material; A2: Add the coating material to anhydrous ethanol and disperse it evenly. Then add 0.1-1% of the coating material mass of silane coupling agent and mix evenly. Then add lanthanum-basalt composite fiber, ultrasonically vibrate for 20-30 minutes, vacuum filter, wash, dry, grind and then add insulator matrix material and mix evenly. Then add water to a ball mill and ball mill for 5-8 hours to obtain the blank mixture. A3: The obtained blank mixture is sieved and iron is removed; then it is successively subjected to pressing, aging, vacuum kneading, shaping, trimming and drying to obtain blanks; A4: The blank is heated to 300-450℃ at a rate of 5-20℃ / h, then heated to 980-1050℃ at a rate of 50-100℃ / h and held for 5-10h, then heated to 1280-1350℃ at a rate of 20-50℃ / h and held for 1-4h in a reducing atmosphere, and then cooled to below 180℃ to obtain the high-voltage ceramic insulator part; A5: The obtained porcelain insulator parts are glued, cured, tested, and packaged to obtain high-voltage ceramic insulators.

7. The method for preparing a high-voltage ceramic insulator according to claim 6, characterized in that: The mass ratio of dopamine hydrochloride, hexagonal boron nitride-titanium dioxide modified compound, and tris(hydroxymethyl)aminomethane solution in A1 is (2-3):1:(18-19).

8. The method for preparing a high-voltage ceramic insulator according to claim 7, characterized in that: The mass concentration of the trihydroxymethylaminomethane solution is 9-10%.

9. A method for preparing a high-voltage ceramic insulator according to claim 6, characterized in that: The silane coupling agent is aminopropyltriethoxysilane.